Pseudodynamic tests on a full-scale 3-storey precast concrete building: global response - Negro, Paolo; Bournas, Dionysios A.; Molina, Francisco J. (Elsevier, 2013)
In the framework of the SAFECAST Project, a full-scale three-storey precast building was subjected to a series of pseudodynamic (PsD) tests in the European Laboratory for Structural Assessment (ELSA). The mock-up was constructed in such a way that four different structural configurations could be investigated experimentally. Therefore, the behaviour of various parameters like the types of mechanical connections (traditional as well as innovative) and the presence or absence of shear walls along with the framed structure were investigated. The first PsD tests were conducted on a dual frame-wall precast system, where two precast shear wall units were connected to the mock up. The first test structure sustained the maximum earthquake for which it had been designed with small horizontal deformations. In the second layout, the shear walls were disconnected from the structure, to test the building in its most typical configuration, namely with hinged beam–column connections by means of dowel bars (shear connectors). This configuration was quite flexible and suffered large deformations under the design level earthquake. An innovative connection system, embedded in the precast elements, was then activated to create emulative beam–column connections in the last two structural configurations. In particular, in the third layout the connectors were restrained only at the top floor, whereas in the fourth layout the connection system was activated in all beam–column joints. The PsD test results showed that, when activated at all the floors, the proposed connection system is quite effective as a means of implementing dry precast (quasi) emulative moment-resisting frames.